Theodor Herzl : from assimilation to Zionism - Kornberg, Jacques, 1933- (Indiana University Press, 1993)
How did Theodor Herzl, an assimilated German nationalist in the 1880s, suddenly in the 1890s become the founder of Zionism? Jacques Kornberg offers a novel and provocative explanation in Herzl's struggle to resolve his own personal conflict over his Jewish identity. Kornberg charts Herzl's intellectual development against the background of Austrian political history from the late 1870s through 1896, the date of his revolutionary manifesto, The Jewish State. As a Viennese aesthete and writer in the 1880s, Herzl sought to shed the taint of Jewish materialism and to distance himself from less assimilated Jews. The rise to power of the anti-semitic Christian Social Party in the 1890s started Herzl on the road to a new self-transformative Jewish politics. Kornberg attributes particular significance to Herzl's 1894 play, The New Ghetto, as marking a definitive break with the idea of Austro-German assimilation. In Kornberg's view the play reveals for the first time Herzl's vision, later defined in The Jewish State, that the virtues he previously believed Jews were to gain through assimilation - independence, physical courage, idealism - were now to be realized by the founding of a secular Jewish state.
Keywords: Herzl, Theodor, -- 1860-1904.; Herzl, Theodor, -- 1860-1904; Herzl, Theodor.; Zionists -- Austria -- Biography.; Sionistes -- Autriche -- Biographies.; POLITICAL SCIENCE -- Political Ideologies -- Nationalism.; BIOGRAPHY & AUTOBIOGRAPHY -- Political.; Zionists; Austria; Zionismus; Zionisme.; 15.70 history of Europe.; Herzl, -- 1860-1904; Zionists -- Austria -- Biography; Biographies; Biografieën (vorm); Biographies.